1985
DOI: 10.1111/j.1752-0606.1985.tb00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Spouses' Cognitive Styles and Marital Interaction Patterns*

Abstract: This study explored the relationship between spouses' cognitive styles and interaction patterns that were characteristic of their marriage. Three measures of cognitive style and one measure of relational interaction patterns were used. Participants were 60 married couples. Results indicated that spouses' reports of parallel, complementary and symmetrical interaction could each be predicted from spouses' intolerance of ambiguity. Husbands reported more parallel interaction when more similar to their wives in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Only limited research (for example, Tyndall & Lichtenberg, 1985) has attempted to identify cognitive and personality factors associated with significant forms of marital interaction. Further, little or no published research has examined the relationship between cognitive complexity and communication among married couples.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited research (for example, Tyndall & Lichtenberg, 1985) has attempted to identify cognitive and personality factors associated with significant forms of marital interaction. Further, little or no published research has examined the relationship between cognitive complexity and communication among married couples.…”
Section: Discussionmentioning
confidence: 99%
“…Karney and Gauer (2010) defined complex cognition by higher levels of differentiation (perceiving more categories or kinds of information from analyzing a given event or person) and integration (connecting or synthesizing different qualities and characteristics). Similarly, Tyndall and Lichtenberg (1985) sug gested that couples who exhibited higher cognitive flexibility by a high tolerance for ambiguity showed more adaptable interpersonal strategies in their relationship when confronted with a change of circumstances.…”
Section: Postformal Thought and Romantic Relationshipsmentioning
confidence: 92%
“…In a review of 40 studies conducted across a variety of domains, Burleson (1987) concluded that “extant research has firmly established the existence of a significant, stable, and substantial relationship between cognitive complexity and person‐centered communication” (p. 306). Research that has specifically addressed communication in established marriages (Denton, Burleson, & Sprenkle, 1995; Martin, 1992; Tyndall & Lichtenberg, 1985) also suggests that spouses whose cognitions about relationships are more complex are more effective at discussing and resolving problems, although none of these studies controlled for concurrent marital satisfaction. Most recently, Campbell, Butzer, and Wong (2008) used a card sorting task to assess the structure of spouses' perceptions of each other and found that, even after controlling for their global evaluations, spouses in established marriages whose perceptions of each other's positive and negative traits were more integrated behaved more positively during discussions of marital problems.…”
Section: Cognitive Content and Cognitive Structure In Intimate Relatimentioning
confidence: 99%